The Influence of the Application of Problem Based Learning Towards the Students’ Speaking Abilty of Grade Eleven of SMA Negeri 5 Bandar Lampung - Sumardi Hussein (International Conference on Education and Language (ICEL), 2014)
The students got confused and felt affraid to speak English. It meant that students’ bravery was needed to improve their speaking ability. The application of Problem Based Learning (PBL) approach might be appropriate to be applied to solve the problem because PBL had several principles that could improve the students’ speaking ability. The objective of this research aimed to find out the influence of the application of Problem Based Learning towards the students’ speaking ability of grade eleven of SMA N 5 Bandar Lampung in academic year 2013-2014.Data were collected by incorporating two pre-tests and two post tests in experimental group and control group. Treatment using Problem Based Learning was administered in experimental group, while control group received by standard teaching. Data analysis was attempted using t-Test for two group design.Result indicated that p-value 1% = 2.65, 5% = 2.00 and t-value = 3.92. It meant that p-value was smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The researcher concluded that the influence of the application of Problem Based Learning (PBL) was more effective than standard teaching.It could be concluded that teaching speaking through Problem Based Learning (PBL) was quite success. It could be seen in the students’ speaking scores that they who learnt speaking through Problem Based Learning had a significant difference. It meant that there was influence of using Problem Based Learning in teaching speaking. Therefore,English teacher should apply cooperative learning using Problem Based Learning (PBL) to teach English in the classroom to make the class more interesting and help the students’ improve their speaking ability.